(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
This paper reviews the underpinning theories and past literature on self-directed learning in relation to self-efficacy by distance learner in higher learning institutions. There is little research available that systematically traces the extent to which individual and external factors play a role in level of self-directed learning ability. Subsequently, a number of hypotheses and a framework of self-directed learning are proposed. There are four hypotheses proposes which are there is a positive significant effect of motivation of self-directed learning; there is a significant positive effect of life satisfaction with self-directed learning; there is a mediate effect of self-efficacy which is significant and positive between motivation with self-directed learning; and there is a mediate effect of self-efficacy which is a significant and positive between life satisfaction and self-directed learning. The paper proposes that the students self-directed learning is influenced by or have relationship with students motivation and life satisfaction.